Volume 5: Manufacturing Materials and Metallurgy; Marine; Microturbines and Small Turbomachinery; Supercritical CO2 Power Cycle 2012
DOI: 10.1115/gt2012-69222
|View full text |Cite
|
Sign up to set email alerts
|

Design and Investigations of a Micro-Turbine Flow Part

Abstract: The co-generative micro-power plant with the HFE7100 as a working medium was designed and built for experimental investigations. The heat output of the plant was assumed equal to 20 kW, while the electric output amounted to about 3kW. In the paper a multi-stage micro-turbine with partial admission of all the stages is described in detail and the results of the particular experimental investigations and numerical calculations are shown, followed by an appropriate discussion and conclusions. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This also applies to devices used in distributed power generation, which additionally should be small in size and have a low impact on the surrounding environment (i.e., low noise and emissions). As far as cogeneration systems and trigeneration systems (in which heat energy is generated simultaneously with electricity and cold) are concerned, such requirements can easily be met by using high-speed fluid-flow machines such as microturbines (Kiciński, 2015, Kosowski et al, 2018, Włodarski, 2018. In order to enable microturbine rotors to operate at increasingly higher rotational speeds, novel bearing systems must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to devices used in distributed power generation, which additionally should be small in size and have a low impact on the surrounding environment (i.e., low noise and emissions). As far as cogeneration systems and trigeneration systems (in which heat energy is generated simultaneously with electricity and cold) are concerned, such requirements can easily be met by using high-speed fluid-flow machines such as microturbines (Kiciński, 2015, Kosowski et al, 2018, Włodarski, 2018. In order to enable microturbine rotors to operate at increasingly higher rotational speeds, novel bearing systems must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that it is possible to build a set of microturbines with a capacity of about 2 kW with higher efficiency than in existing machines [74]. It is worth noting that the relatively high efficiency of microturbines can be achieved due to a very careful and advanced design process.…”
Section: Resultsmentioning
confidence: 99%
“…At present, due to coal-fired plants, the power systems in many countries, are characterized by a relatively low efficiency [1,2]. In the case of distributed energy systems, however, the efficiency of electricity production is even lower [3][4][5], and the Organic Rankine Cycle power plants achieve the efficiency which exceeds 10% [6][7][8] (seldom about 20%). Higher values of efficiency are obtained by ultra-supercritical steam turbine power plants [9,10], combined gas-steam thermal cycles [11] or modified ORC cycles [12].…”
Section: Introductionmentioning
confidence: 99%
“…The values of initial pressure and temperature have been determined taking into account particular schema of the cycle, media stability limitation and the maximum value of the cycle efficiency. The pressure in the condenser has been estimated assuming the temperature of the cooling water equal to 15 • C. The efficiencies of particular elements (typical of micro power plants) are shown in Table 1 [3,4,6,7,27]. • 1,1,1,3,3-pentafluorobutane (chemical formula-C4H5F5, commercial name-R365mfc, [24]); • Methylcyclohexane (chemical formula-C7H14, commercial name-c1cc6, [24]); • N-propylcyclohexane (chemical formula-C9H18, commercial name-c3cc6, [24]); • Undecane (chemical formula-C11H24, commercial name-C11, [24]); • 1-chloro-3,3,3-trifluoroprop-1-ene (chemical formula-C3H2ClF3, commercial name-R1233zd, [25]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation